The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.orglett.2c01243
|View full text |Cite
|
Sign up to set email alerts
|

Borane- and Silylium-Catalyzed Difunctionalization of Carbohydrates: 3,6-Anhydrosugar Enabled 1,6-Site Selectivity

Abstract: A novel diastereoselective, Lewis acid catalyzed 1,6-difunctionalization of galactose and mannose derivatives has been developed in one pot, via sequential nucleophile additions. Our studies point to the formation of a 3,6-anhydrosugar intermediate as key to the 1,6-site-selectivity. Starting material-specific reactivity occurs when competitive ring-opening C–O cleavage is possible, owed to basicity and stereoelectronic stabilization differences. Lastly, Mayr nucleophilicity parameter values helped predict whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The observation that the BAr 3 -initiated reaction is significantly faster than the TMS-OTf catalyzed reaction suggests the importance of weakly coordinating fluorinated triarylborate counterions (e.g., 37 ) formed in situ . The question of whether boranes act as catalysts or as initiators has been raised before, and both computations and experiments have indicated that B­(C 6 F 5 ) 3 ( 6 ) is more often an initiator than a catalyst, e.g., in group transfer reactions. In that context, our study on borane-initiated conjugate addition reactions highlights that the Lewis acidity of an initial Lewis acid catalyst does not necessarily relate to its catalytic activity in a reaction, and other factors like the Lewis acidity or electrophilicity of species formed in situ or the coordinating ability of intermediates are of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that the BAr 3 -initiated reaction is significantly faster than the TMS-OTf catalyzed reaction suggests the importance of weakly coordinating fluorinated triarylborate counterions (e.g., 37 ) formed in situ . The question of whether boranes act as catalysts or as initiators has been raised before, and both computations and experiments have indicated that B­(C 6 F 5 ) 3 ( 6 ) is more often an initiator than a catalyst, e.g., in group transfer reactions. In that context, our study on borane-initiated conjugate addition reactions highlights that the Lewis acidity of an initial Lewis acid catalyst does not necessarily relate to its catalytic activity in a reaction, and other factors like the Lewis acidity or electrophilicity of species formed in situ or the coordinating ability of intermediates are of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on 1,2-additions (Scheme A), neither the change of the catalytically active species during the reaction has been directly observed nor have the kinetics of individual reaction steps been evaluated. Since competing metal vs silylium activation also arises in Lewis acid-catalyzed conjugate additions , and has also been reported with borane catalysts in other precedents, , we have now performed an extensive mechanistic investigation of the borane-initiated 1,4-additions of allylsilanes and silyl enol ethers to α,β-unsaturated carbonyl compounds, the electrophilic reactivities of which have previously been quantified by us …”
mentioning
confidence: 99%
“…The development of chemoselective reduction reactions is an important objective in organic synthesis. 1,2 The ability to diversify oxidized precursors into distinct products or to control the extent of reduction in systems with multiple sites of reactivity can streamline syntheses by avoiding unnecessary redox adjustments. In particular, the chemoselective conjugate reduction of enones plays an important role in the synthesis of aliphatic ketones, which are prevalent in biologically active compounds.…”
mentioning
confidence: 99%